Synthesizing, Structuring, and Characterizing Bioactivities of .Cr(III), La(III), and Ce(III) .Complexes with Nitrogen, Oxygen .and Sulpher donor bidentate Schiff base ligands (Baghdad Science Journal, 2021)
Two Schiff bases, namely, 3-(benzylidene amino) -2-thioxo-6-methyl 2,5-dihydropyrimidine-4(3H)-one (LS])and 3-(benzylidene amino)-6-methyl pyrimidine 4(3H, 5H)-dione(LA)as chelating ligands), were used to prepare some complexes of Cr(III), La(III), and Ce(III)] ions. Standard physico-chemical procedures including metal analysis M%, element microanalysis (C.H.N.S) , magnetic susceptibility, conductometric measurements, FT-IR and UV-visible Spectra were used to identify Metal (III) complexes and  Schiff bases (LS) and (LA). According to findings, a [Cr(III) complex] showed six coordinated octahedral geometry, while [La(III), and Ce(III) complexes]were structured with coordination number seven.  Schiff's bases and mineral complexes were examined in vitro to investigate potential inhibition against Gram-positive bacteria such as Pseudonomous aerugionosa and Gram-negative bacteria such as Staphylococcus aureus. The low concentration for inhibition has been also determined by studying the minimal inhibitory concentrations MIC .Antibiotics (Ampicillin, Amoxicillin) have been chosen to contrast their activity. Furthermore, Anti-fungal activity against two types of fungi ʺAspergillus flavusʺ and ʺPenicillum Spp.ʺ was studied for these compounds. The results of the antibacterial activity were better compared to the standard drugs.